Emprendimiento en Perú antes y durante la Covid-19: Eterminantes, brecha en ingresos y eficiencia técnica; Entrepreneurship in Peru before and during Covid-19: Determinants, income gap and technical efficiency - Luis Barriga; Juliana Bautista; Ignacio Aguaded (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– It is implausible that the spread of Covid-19 has not had an impact on entrepreneurship in Peru, considering that on average 41.1 % of the Economically Active Population is engaged in starting their own businesses. The objectives of this research are as follows: To estimate the influencing factors for individuals to become entrepreneurs through probabilistic regression models. To quantify the gender income gap in entrepreneurship using the Blinder-Oaxaca decomposition. Finally, to calculate the technical efficiency in the production of entrepreneurial activities using stochastic frontier models. The National Household Survey conducted annually by the National Institute of Statistics and Informatics in Peru was utilized, with a sample size of 21,243 entrepreneurs in 2019, 9,935 in 2020, and 18,042 in 2021. The highlighted results are as follows: Firstly, variables such as age and being the head of a household increase the likelihood of both men and women becoming entrepreneurs. On the other hand, the gender income gap was 78.0 % in favor of men in 2019, 75.5 % in 2020, and 76.4 % in 2021. Lastly, in 2019 and 2020, the highest average technical efficiency, i.e., the percentage of total maximum achievable production, was observed in the commerce sector (79.5 % and 7.94 %, respectively), and in 2021, it was in the services sector (83.9 %). Additionally, at the gender level, women exhibit higher efficiency in production and services activities.
Keywords: C21; C25; J16; L26; 330; Entrepreneurship; income gap; technical efficiency; gender; Blinder-Oaxaca